P0804TRENDS IN BODY MASS INDEX IN PATIENTS WITH INCIDENT CHRONIC AND END STAGE KIDNEY DISEASE FROM 2004 - 2019. (6th June 2020) - Gamio-Izasmendi, Diana; Gillis, Keith; Mark, Patrick; McManus, Siobhan; Traynor, Jamie
Abstract: Background and Aims: Obesity is increasingly prevalent in the general population. Body mass index (BMI) has a U-shaped relationship with mortality in chronic kidney disease (CKD), but also has implications for service delivery. We analysed the BMI trends in incident patients referred to CKD clinic (CKD), starting haemodialysis (HD), peritoneal dialysis (PD) and receiving a kidney transplant (Tx). Our aim was to establish the trend in BMI across these specified patient groups over the last 15 years. Method: A single centre retrospective analysis was carried out including adults referred to secondary care nephrology services between 2004 and 2019. Patients were categorised into CKD, HD, PD, or Tx. Those reaching ESKD were grouped according to first method of renal replacement therapy (RRT). Patients with acute kidney injury and with missing BMI data were excluded. As per the World Health Organisation's definition, BMI was categorised into classes I, II and III (>30, 35, and 40kg/m 2 respectively). Results: Of 10, 057 patients, 6, 936 patients were included. Of these, 59.96% (n=4, 249) were CKD, 7.39% (n=524) were Tx, 4.85% (n=344) were PD, and 27.43% (n=1, 944) were HD. BMI was 27.3±7.2kg/m 2 in 2004 and 27.8±7.72kg/m 2 in 2019 with no significant change in BMI as a whole throughout that time period (p=0.07). In subgroup analysis, there was no change in BMI in the CKD (p=0.52) or PD (0.76) groups. However, there was a significant increase in BMI seen in both the HD (p<0.001) and Tx (p=0.006) groups. An increase in the proportion of patients with class III obesity was also observed in the HD group (p=0.009) but not the CKD, Tx or PD groups. Conclusion: In contrast to the general population, the prevalence of obesity has not changed in incident patients with kidney disease over the last 15 years. In subgroup analysis however, there is a trend towards rising BMI in the incident haemodialysis patient group. Limitations of the study include retrospective design, lack of ethnicity data, and inclusion of only a single measure of adiposity. Although the relationship between BMI and mortality in patients receiving maintenance haemodialysis is non-linear, the increase in the very obese in this patient group will have significant implications for healthcare providers.